PENGARUH PRODUK WISATA, PERSEPSI HARGA DAN PROMOSI WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI SPOT DESA WISATA LIYA TOGO DAN SPOT WISATA PULAU KAPOTA KABUPATEN WAKATOBI - La Ane; Umar Wirahardi Kusuma; Astuti; Ulpiana Ulpiana; Ridwan Hasa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Tourism is a strategic sector that plays a significant role in promoting regional economic growth by increasing community income, creating employment opportunities, and developing local potential in a sustainable manner. Wakatobi Regency is recognized as one of Indonesia’s leading marine tourism destinations, characterized by its rich marine ecosystems, coastal culture, and diverse tourist attractions. However, tourists’ visiting decisions are influenced by the quality of tourism products, price perceptions, and the effectiveness of destination promotion. This study aims to analyze the influence of tourism products, price perception, and tourism promotion on tourists’ visiting decisions at Liya Togo Tourism Village and Kapota Island, Wakatobi Regency. A quantitative approach with a survey method was employed involving 44 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS. The findings are expected to contribute both theoretically to tourism marketing studies and practically to destination managers and local governments in developing sustainable tourism marketing strategies based on local potential.